Socially dangerous consequences of a breach of the rules of safety the movement and operation of air transport (article 276 of the Criminal Code of Ukraine) - Лихова, С. Я.; Рощина, І. О. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
This article provides an analysis of the socially dangerous consequences in the corpus delict (article 276of the Criminal code of Ukraine). Discusses issues of conformity of the criminal and air law terminology inUkraine.